Mitodepressive effect and chromosomal aberrations induced by KBrO3 on A. sativum Lroot tips - Khatab, Hoda; Hamed, Samia; Elhaddad, Nagat (Libyan Journal of Science &Technology, 2022)
Mitodepressive effect and chromosomal aberrations induced by KBrO3 on A. sativum Lroot tips